Attachment styles in children affected by migraine without aura - Esposito M (Dove Medical Press, 2013)
Maria Esposito,1 Lucia Parisi,2 Beatrice Gallai,3 Rosa Marotta,4 Anna Di Dona,1 Serena Marianna Lavano,2 Michele Roccella,4 Marco Carotenuto11Center for Childhood Headache, Clinic of Child and Adolescent Neuropsychiatry, Department of Mental Health, Physical and Preventive Medicine, Second University of Naples, Naples, Italy; 2Child Neuropsychiatry, Department of Psychology, University of Palermo, Palermo, Italy; 3Unit of Child and Adolescent Neuropsychiatry, University of Perugia, Perugia, Italy; 4Department of Psychiatry, The Magna Graecia University of Catanzaro, Catanzaro, ItalyBackground: In recent years, great attention has been given to the presence of psychological problems and psychiatric comorbidity that are also present in children affected by primary headaches. The relationship between pain and attachment has been identified, and it may be that pain perception may change in relation with specific attachment styles. The aim of the present study was to assess the prevalent attachment style and verify its putative relationship and correlation with the main characteristics of migraine attacks, in school-aged children affected by migraine without aura (MoA).Materials and methods: The study population consisted of 219 children (103 males, 116 females) aged between 6 and 11 years (mean 8.96 ± 2.14 years), consecutively referred for MoA compared with 381 healthy controls (174 males, 207 females; mean age 9.01 ± 1.75 years) randomly selected from schools. All the children were classified according to the attachment typologies of the Italian modified version of the Separation Anxiety Test; monthly headache frequency and mean headache duration were assessed from daily headache diaries kept by all the children. Headache intensity was assessed on a visual analogue scale. The chi-square test and t-test, where appropriate, were applied, and the Spearman rank correlation test was applied to explore the relationship between the types of attachment style and clinical aspects of MoA.Results: The MoA group showed a significantly higher prevalence of type A (avoidant) attachment (P<0.001) and a significantly lower prevalence of type B (secure) attachment (P<0.001) compared with the control group. Moreover, the Spearman rank correlation analysis showed a significant relationship between MoA characteristics and the attachment style of MoA children.Conclusion: The main findings of the present study were the higher prevalence among MoA children of the avoidant attachment style (type A) and the significantly lower prevalence of the secure style attachment (type B) compared with the normal controls, suggesting that the study of psychiatric comorbidity in pediatric headache may be enriched by this new aspect of analysis.Keywords: migraine without aura, children, attachment style, Separation Anxiety Test